Complementation of hypersensitivity to DNA interstrand crosslinking agents demonstrates that XRCC2 is a Fanconi anaemia gene. Issue 10 (20th May 2016) - Park, Jung-Young; Virts, Elizabeth L; Jankowska, Anna; Wiek, Constanze; Othman, Mohamed; Chakraborty, Sujata C; Vance, Gail H; Alkuraya, Fowzan S; Hanenberg, Helmut; Andreassen, Paul R
Abstract : Background: Fanconi anaemia (FA) is a heterogeneous inherited disorder clinically characterised by progressive bone marrow failure, congenital anomalies and a predisposition to malignancies. Objective: Determine, based on correction of cellular phenotypes, whether XRCC2 is a FA gene. Methods: Cells (900677A) from a previously identified patient with biallelic mutation of XRCC2, among other mutations, were genetically complemented with wild-type XRCC2. Results: Wild-type XRCC2 corrects each of three phenotypes characteristic of FA cells, all related to the repair of DNA interstrand crosslinks, including increased sensitivity to mitomycin C (MMC), chromosome breakage and G2–M accumulation in the cell cycle. Further, the p.R215X mutant of XRCC2, which is harboured by the patient, is unstable. This provides an explanation for the pathogenesis of this mutant, as does the fact that 900677A cells have reduced levels of other proteins in the XRCC2–RAD51B-C-D complex. Also, FANCD2 monoubiquitination and foci formation, but not assembly of RAD51 foci, are normal in 900677A cells. Thus, XRCC2 acts late in the FA–BRCA pathway as also suggested by hypersensitivity of 900677A cells to ionising radiation. These cells also share milder sensitivities towards olaparib and formaldehyde with certain other FA cells. Conclusions: XRCC2/FANCU is a FA gene, as is another RAD51 paralog gene, RAD51C/FANCO . Notably, similar to a subset of FA genes that act downstream of FANCD2, biallelic mutation of XRCC2/FANCU has not been associated with bone marrow failure. Taken together, our results yield important insights into phenotypes related to FA and its genetic origins.